2016
DOI: 10.1166/jnn.2016.10765
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Gas Sensing Properties of Hollow ZnS Microspheres

Abstract: Hollow ZnS microspheres are synthesized by a facile hydrothermal method. Morphology and structure of the ZnS microspheres are analyzed by SEM, TEM, XRD and N2 sorption technique, Gas sensing properties of the as-prepared ZnS sensor are also systematically investigated. The results show that the ZnS microspheres have well-developed porous and hollow nanostructure. The sensor based on the ZnS microspheres exhibits ultra-fast response (1-2 s) and fast recovery time (7-34 s) towards ethanol at the optimal operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Currently, based on II–VI compounds, a variety of 3D structures have been synthesized and used for the development of gas sensors. These 3D structures include hierarchical nanostructures [ 57 , 58 , 85 , 86 ], hollow spheres [ 87 , 88 ], and core/shell nanostructures [ 89 , 90 , 91 ]. These developments have shown that this direction is indeed very promising.…”
Section: Current Statusmentioning
confidence: 99%
“…Currently, based on II–VI compounds, a variety of 3D structures have been synthesized and used for the development of gas sensors. These 3D structures include hierarchical nanostructures [ 57 , 58 , 85 , 86 ], hollow spheres [ 87 , 88 ], and core/shell nanostructures [ 89 , 90 , 91 ]. These developments have shown that this direction is indeed very promising.…”
Section: Current Statusmentioning
confidence: 99%
“…Among the materials proposed for this purpose, the zinc sulfide (ZnS) semiconductor materials have a wide bandgap of about 3.6 eV and exhibit highly tunable chemical and physical properties as well as unique functionalities for a huge variety of emerging technologies (Chen et al, 2010;Hussain et al, 2017;Ippen et al, 2014;Jellison et al, 1986;La Porta et al, 2014a;Lee and Wu, 2017;Lin et al, 2019;Sultana et al, 2018;Xiao et al, 2016;Zhang et al, 2013;Ziegler et al, 2008). A notable example of ZnS-related applications includes light-emitting diodes (LEDs), lasers, sensors, solar cells, piezoelectric nanogenerator, (photo)catalysis, and biomedical applications (Hussain et al, 2017;Ippen et al, 2014;Jellison et al, 1986;La Porta et al, 2014a;Lee and Wu, 2017;Lin et al, 2019;Sultana et al, 2018;X.…”
Section: Introductionmentioning
confidence: 99%
“…A notable example of ZnS-related applications includes light-emitting diodes (LEDs), lasers, sensors, solar cells, piezoelectric nanogenerator, (photo)catalysis, and biomedical applications (Hussain et al, 2017;Ippen et al, 2014;Jellison et al, 1986;La Porta et al, 2014a;Lee and Wu, 2017;Lin et al, 2019;Sultana et al, 2018;X. Wang, et al, 2011;Xiao et al, 2016;Zhang et al, 2013;Ziegler et al, 2008). Furthermore, more recently, the ZnS-based heterostructure have been widely studied, mainly due to high quality of ZnS shell (in core/shell structures with a lower bandgap core) that contributes to an increase in the efficiency and stability of optoelectronic devices based on ZnS heterostructures (Chen et al, 2021;Mukherjee and Selvaraj, 2021;Talapin et al, 2004;P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation